2012
DOI: 10.1177/1528083712438069
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of embroidered textile electrodes for continuous measurement of electrocardiogram signals

Abstract: Textile electrodes are a new and potential choice for long term and continuous monitoring of electrocardiogram measurements. In this research, textile electrodes have been designed and developed by embroidering conductive yarn on the polyester fabric to measure electrocardiogram biosignals of patients. Silver-coated nylon thread is embroidered on 100% polyester fabric in square form 11 mm  11 mm with satin stitches in order to form three heart vectors (V3, V4, and V5). These electrodes are characterized based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 10 publications
1
51
2
Order By: Relevance
“…The textile sensors as substrate devices are likely to contact with the human body in a noninvasive method, such as shirts [11,12], gloves [13], and band type [14,15]. The textile sensor is classified into four significant areas according to the textile structure and pattern as follows: dyeing [16], knitting [17], weaving [18], and embroidery [19]. In particular, the embroidery technique can make three-dimensional patterns on the textile surface via post processing as compared with the printing, knitting, and weaving techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The textile sensors as substrate devices are likely to contact with the human body in a noninvasive method, such as shirts [11,12], gloves [13], and band type [14,15]. The textile sensor is classified into four significant areas according to the textile structure and pattern as follows: dyeing [16], knitting [17], weaving [18], and embroidery [19]. In particular, the embroidery technique can make three-dimensional patterns on the textile surface via post processing as compared with the printing, knitting, and weaving techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is likelihood that there may be gel residues on skin that may cause a short circuit of electrodes. Another drawback of using Ag/AgCl electrode is its short serve time that cannot be used for long-time monitoring of human in sleeping or working conditions [12,13]. In addition, Ag/AgCl electrode for ECG measurement process is uncomfortable and painful for patients because the skin preparation for attaching such electrode habitually occupies an abrasion to the external skin layer.…”
Section: Introductionmentioning
confidence: 99%
“…A motion sensor was also integrated within the fabric in order to detect the change of skin-electrode impedance accurately. Kannaian et al [13] proposed an approach of using embroidery stitch on the surface of polyester fabric with 75 D longitudinal density and 150 D horizontal density for electrodes using Wilcom Embroidery software. Such electrodes were compared with commercial Ag/AgCl electrode for the performances in terms of electrode position, cleaning, signal quality, spin supplies, and repeatability.…”
Section: Introductionmentioning
confidence: 99%
“…Some research projects have also demonstrated opportunities to apply the embroidery technology for the development of textile antenna and coil for magnetic resonance sensors (12) − (16), (19). (20), (21), (23) − (25), (29) − (38). Sensing properties of textiles and compounds developed from textile materials are of great importance in protective and medical functional clothing and textiles (9).…”
Section: Introductionmentioning
confidence: 99%